The modular approach enables a fully ab initio simulation of the contacts between 3D and 2D materials - Fediai, Artem; Ryndyk, Dmitry A.; Cuniberti, Gianaurelio (Journal of Physics: Condensed Matter, 2016)
Up to now, the electrical properties of the contacts between 3D metals and 2D materials have never been computed at a fully ab initio level due to the huge number of atomic orbitals involved in a current path from an electrode to a pristine 2D material. As a result, there are still numerous open questions and controversial theories on the electrical properties of systems with 3D/2D interfaces - for example, the current path and the contact length scalability. Our work provides a first-principles solution to this long-standing problem with the use of the modular approach, a method which rigorously combines a Green function formalism with the density functional theory (DFT) for this particular contact type. The modular approach is a general approach valid for any 3D/2D contact. As an example, we apply it to the most investigated among 3D/2D contacts - metal/graphene contacts - and show its abilities and consistency by comparison with existing experimental data. As it is applicable to any 3D/2D interface, the modular approach allows the engineering of 3D/2D contacts with the pre-defined electrical properties.
CRIS-Team Scopus Importer:2023-03-20
Keywords: contact length scaling; contacts; DFT; extended contacts; grapheme; Green function method; two-dimensional materials